2022
DOI: 10.3389/fmicb.2021.718776
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the Bladder Microbiota in Patients With Bladder Cancer

Abstract: Evidence suggests that microbiota may contribute to the pathogenesis of several diseases, including cancer. In the case of bladder cancer, preliminary studies have found alterations in the urinary microbiota of patients with urothelial carcinoma compared with healthy individuals. Conversely, the urinary microbiota differ between men and women, and it has been hypothesized that these differences are associated with the lower incidence of bladder cancers in women. The objective of this study was to characterize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 40 publications
1
23
1
Order By: Relevance
“…Parra-Grande et al have reported that the amount of Actinobacteria is much higher in non-neoplastic bladder mucosa specimens than in tumor tissues, 45 supporting the hypothesis that Actinomycete -rich microbes associated with a lower incidence of BCa in women might have a preventive effect against BCa. Pederzoli et al 46 have demonstrated noticeable cluster differences in urine and tissue samples between males and females, implicating intersexual differences in microbiome that may explain the reduced prevalence of BCa in females due to the overall bladder microenvironment.…”
Section: Microbiomes Of Urologic Diseasementioning
confidence: 83%
See 2 more Smart Citations
“…Parra-Grande et al have reported that the amount of Actinobacteria is much higher in non-neoplastic bladder mucosa specimens than in tumor tissues, 45 supporting the hypothesis that Actinomycete -rich microbes associated with a lower incidence of BCa in women might have a preventive effect against BCa. Pederzoli et al 46 have demonstrated noticeable cluster differences in urine and tissue samples between males and females, implicating intersexual differences in microbiome that may explain the reduced prevalence of BCa in females due to the overall bladder microenvironment.…”
Section: Microbiomes Of Urologic Diseasementioning
confidence: 83%
“…Using urine samples (urination and catheterization/cystoscopy), some studies have reported significantly greater α and β diversities. 45 , 56 However, Chipollini et al 57 have demonstrated lower α diversity in BCa compared to matched healthy controls. Wu et al 58 and Zeng et al 59 have shown that richness measures of males with BCa are higher than those of males without cancer.…”
Section: Microbiomes Of Urologic Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a higher abundance of Enterococcus showed in low-grade tumors. Based on these findings, detected microorganisms might play a role in the initial development of bladder cancer ( 170 ). Mansour et al.…”
Section: The Study Of Tumor Microbiome In Various Solid Malignanciesmentioning
confidence: 96%
“…observed a significantly greater abundance of Actinobacteria in nonneoplastic bladder mucosa than in tumor tissues (P = 0.014). Although not statistically significant at the genus level, Propionibacterium was more abundant in the non-tumor mucosa (P = 0.08) ( Parra-Grande et al., 2022 ). Propionibacterium freudenreichii , notable for its probiotic potential and commercial relevance, has been suggested to be a protective agent against colorectal cancer.…”
Section: Phylum Actinobacteriamentioning
confidence: 98%